The Association of Abnormal Ventricular Wall Motion and Increased Dispersion of Repolarization in Humans is Independent of the Presence of Myocardial Infarction - Opthof, Tobias; Sutton, Peter; Coronel, Ruben; Wright, Susan; Kallis, Panny; Taggart, Peter (Frontiers in Physiology, 2012)
Abnormal ventricular wall motion is a strong clinical predictor of sudden, arrhythmic, cardiac death. Dispersion in repolarization is a prerequisite for the initiation of re-entrant arrhythmia. We hypothesize that regionally decreased wall motion is associated with heterogeneity of repolarization. We measured local activation times, activation recovery intervals (ARIs, surrogate for action potential duration) and repolarization times (RT) using a multielectrode grid at 9 segments on the left ventricular epicardium in 23 patients undergoing coronary artery surgery. Regional wall motion was simultaneously assessed using intraoperative transoesophageal echocardiography. Three groups were discriminated: 1) Patients with normal wall motion (n=11), 2) Patients with one or more hypokinetic segments (n=6), 3) Patients with one or more akinetic or dyskinetic segments (n=6). The average ARI was similar in all groups (251±3.7 ms, ±sem). Dispersion of ARIs at the 9 segments was significantly increased in the hypokinetic (84±7.4 ms, p<0.005) and akinetic/dyskinetic group (94±3.5 ms, p<0.0005) compared with the normal group (49±5.1 ms), independent from the presence of myocardial infarction. Repolarization heterogeneity occurred primarily in the normally contracting regions of the hearts with abnormal wall motion. An almost maximal increased dispersion of repolarization was observed when there was only a single hypokinetic segment. We conclude that inhomogeneous wall motion abnormality of even moderate severity is associated with increased repolarization inhomogeneity, independent from the presence of infarction.